Effect of the examination stress on periodontal health status and salivary IL-1? among Iraqi dental students - Mahmood, Athraa A; Ibrahim, Leka'a M (Journal of Baghdad College of Dentistry, 2013)
Background: Periodontal diseases (PD) are common chronic inflammatory diseases caused by pathogenic microorganisms colonizing the gingival area and inducing local and systemic elevations of pro-inflammatory cytokines resulting in tissue destruction by a destructive inflammatory process. Stress was considered as one of the important risk factors that cause many inflammatory diseases including PD. The purpose of this study wasto determines and compares clinical periodontal parameters (PLI, GI and BOP), stress level and salivary IL-1? level among dental students before, during and after mid-year exam, also to find the correlation among stress, IL-1? and clinical periodontal parameters.Materials and methods: The sample was consisted of 24 dental students; 12 male and 12 female aged (21-23) years, theywere examined in this follow up study at three main periods; first period at least one month before mid-year exam (Period I), second period during mid-year exam (Period II) and third period at least one month after mid-year exam (Period III). DASS-21 was used to measure stress level in all periods. Saliva samples were collected to determine the salivary IL-1? level by ELISA. Clinical periodontal parameters were recorded at four sites per tooth.Results: The means of all clinical periodontal parameters were higher in the period II than in the periods I and III with highly significant differencesat (P ? 0.01). As well as, the means concentrations of salivary IL-1? were higher in the period II than in the periods I and III with highly significant differencesat (P ? 0.01). Also, by using Pearson's Correlation Coefficient, stress shows highly significant strong correlation with IL-1? and clinical periodontal parametersat (P ? 0.01).Conclusions: The results of this study provided strong evidence of association between examination stress and PD, where dental students during mid-year exam have higher levels of stress, clinical periodontal parameters and salivary IL-1? as compared with before and after mid-year exam periods.